2022
DOI: 10.3390/f13122175
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficiency of the Push-and-Pull Strategy during Severe Ips typographus Outbreak and Extreme Drought in Norway Spruce Stands

Abstract: Protection of Norway spruce stands using anti-attractants was tested during an outbreak of bark beetles (Ips typographus) in their spring flight. The aims of this study were as follows: (1) to test the proposed experimental design for tree protection; (2) to evaluate height-specific alternatives for dispenser installation on trees; and (3) to evaluate the efficiency of tree protection measures using anti-attractants under bark beetle infestation and drought stress. The experiment was conducted at the forest ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 51 publications
2
16
2
Order By: Relevance
“…Previous studies have shown that when populations were low, enlarging the entry area can increased Drosophila suzukii captures and improved selectivity for D. suzukii (Renkema et al 2014). When areas affected by extremely dense bark beetle populations, the use of antiattractants did not prove effective (Jakuš et al 2022). Suggesting that population density must be taken into account in the testing of attractant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that when populations were low, enlarging the entry area can increased Drosophila suzukii captures and improved selectivity for D. suzukii (Renkema et al 2014). When areas affected by extremely dense bark beetle populations, the use of antiattractants did not prove effective (Jakuš et al 2022). Suggesting that population density must be taken into account in the testing of attractant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Both the push and pull might be enhanced by the addition of new semiochemicals (Jakuš et al, 2022;Deganutti et al, 2023). The addition of (+)-isopinocamphone to the trapping lure could increase beetle attraction away from trees while simultaneously protecting them from an estragole-enhanced beetle repellant.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation pheromone components, produced by male beetles after successful colonization (Birgersson et al, 1984;Ramakrishnan et al, 2022), have been employed for monitoring and controlling I. typographus populations (Heber et al, 2021). Furthermore, recent research has focused on the management potential of kairomones, compounds originating from both host spruce trees and non-host trees, e.g., broadleaf trees (Zhang and Schlyter, 2004;Jakuš et al, 2022). Bark beetles possess a sophisticated olfactory system that enables them to detect and distinguish the chemical composition and quantity of these odors (Andersson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction by anti-attractants on bark beetle-induced tree mortality has been observed in mountainous or boreal landscapes under normal weather conditions [20][21][22]32]. However, in conditions of spruce monocultures in low elevation under drought stress and a high bark beetle population, anti-attractants were not effective [33]. Studies involved the use of dispensers comprising verbenone [20,32] or a blend consisting of verbenone, conophthorin, and GLVs [20][21][22].…”
Section: Introductionmentioning
confidence: 99%